Combination of structure-based virtual screening, molecular docking and molecular dynamics approaches for the discovery of anti-prion fibril flavonoids - Jheng, Cheng-Ping; Lee, Cheng-I (Frontiers in Molecular Biosciences, 2023)
Prion diseases are a group of rare neurodegenerative diseases caused by the structural conversion of cellular prion into Scrapie prion resulting aggregated fibrils. Therapy of prion diseases has been developed for several decades, especially drug designs based on the structure of prion monomers. Unfortunately, none of the designed anti-prion drugs function well clinically. To fight against prion fibrils, a drug design based on the precise structure of mammalian prion fibrils is highly required. Fortunately, based on the advantage of newly advanced cryo-electron microscopy (cryo-EM) in the deconvolution of large complexes, three prion fibril structures were resolved in the last two years. Based on the cryo-EM solved prion fibril structures, we are able to find some molecules fighting against prion fibrils. Quercetin, one flavonoid molecule in the polyphenol group, has been found to disaggregate the prion fibrils in vitro. In this study, we performed the molecular docking and molecular dynamics simulation on quercetin-like molecules possessing pharmacological properties to evaluate the anti-prion ability of tested molecules. As a result, four quercetin-like molecules interact with prion fibril and decrease the beta-strand content by converting some beta-strands into loop and helical structures to disintegrate the existing fibril structure. The results of this study are significant in the treatment of prion diseases, and the approaches used in this study are applicable to other amyloid diseases.